If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 2x + 6 = 4x + 5 + 1 Reorder the terms: 6 + 2x = 4x + 5 + 1 Reorder the terms: 6 + 2x = 5 + 1 + 4x Combine like terms: 5 + 1 = 6 6 + 2x = 6 + 4x Add '-6' to each side of the equation. 6 + -6 + 2x = 6 + -6 + 4x Combine like terms: 6 + -6 = 0 0 + 2x = 6 + -6 + 4x 2x = 6 + -6 + 4x Combine like terms: 6 + -6 = 0 2x = 0 + 4x 2x = 4x Solving 2x = 4x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-4x' to each side of the equation. 2x + -4x = 4x + -4x Combine like terms: 2x + -4x = -2x -2x = 4x + -4x Combine like terms: 4x + -4x = 0 -2x = 0 Divide each side by '-2'. x = 0 Simplifying x = 0
| 8.5+6(20-x)=20(7) | | 4a+b=4 | | 0.75x+0.15(90-x)=90(0.35) | | 6x-10=64 | | 2p-4=44+8p | | Y=-x^2+20x-64 | | 2(2x-5)=2x-10 | | 7y-22=-28+6y | | 0.1r+0.2=0.6 | | 2x+15=45 | | 3x^2-8x-80=0 | | 225-30x-x^2=112.5 | | -x^2-30x-112.5=0 | | 2+(x+5)=-8 | | 0.1x+0.2x+0.3x=6 | | x^2-30x-112.5=0 | | -18n^2-15n+7=0 | | 2/5(25z-30)=3/4(12z+16) | | 7a-4a+5=6+7a-9a+1 | | 2y=-8y+10 | | 6y=-7y+13 | | -5w+1=-4 | | -1.5w+3=2.5w-1 | | -12-4=-t-t | | -4w=1 | | 0=-6y+34 | | C(x)=81x+1973 | | 9u+17=-5u+7 | | 6(3x+5)=5(x-4)+18 | | 4+2(-9z+4)=4(-z-1)-1 | | -3.6u+1.8=-1.8 | | -0.7-5.6=-3.5 |